Utilization of modified starch in the improvement of banana sherbet characteristics - Castillo, Aileen May F.; Benedicto, Ana Marie Q. (2002., 2002)
ABSTRACT This study aims to utilize modified starch in the improvement of banana sherbet characteristics in terms of texture, melting quality and percent overrun. The study was divided into three phases. Phase I determined the optimum ratio of milkfat to modified starch evaluating samples of different ratios of milkfat to modified through sensory evaluation using 9-pt hedonic scaling. From the Analysis of Variance (ANOVA) of the results, sample having 50:50 ratio of milkfat to modified starch was selected best. The selected formulation was then standardized in Phase II, again through sensory evaluation using 9-pt hedonic scaling and presented to 40 panelists. Melting quality and percent overrun were also determined. Overall, the samples were rated like slightly to moderately. Melting test result was 13.69 ml drippings per 30 minutes while overrun reached 35.92%. In Phase III, the selected sample was subjected to physical and chemical analysis where total solids and fat content were analyzed using the Gravimetric method and Mojonnier method respectively. Color was determined using Munsell book of colors. To determine the feasibility of the product, cost analysis was made comparing cost of the selected sample and that of the control. Fat content result of the selected sample is 0.5% while that of the control is 1.3%. On the other hand, the total solids of the selected sample is higher than the control. Cost of the product containing 50% modified starch is higher than that of control. However, the cost is not significantly different. In this regard, substituting 50% of milkfat with 50% of modified starch in sherbet will not only improve the qualities of the product such as melting, texture, smoothness and overrun but will promote less calorie food.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Starch; Sherbets